Signal Order Optimization of Interconnects Enabling High Electromagnetic Compatibility Performance in Modern Electrical Systems - Ludovica Illiano; Xiaokang Liu; Xinglong Wu; Flavia Grassi; Sergio Amedeo Pignari (Energies, 2024)
Flexible flat cables (FFCs) are a typical form of interconnect in modern electrical and electronic systems that facilitate signal transmission between components while minimizing harness volume. FFCs offer a practical connectivity solution in energy management applications, where sensors and displays are essential for monitoring power consumption and performing advanced digital control. In FFCs, signal lines run parallel to each other, and the proximity between lines can cause interference among adjacent signals. Therefore, the arrangement of signals along different lines can significantly influence the overall transmission performance. In this paper, the order of signals within the FFC is optimized to ensure optimal transmission performance, avoiding electromagnetic compatibility (EMC) and signal integrity (SI) issues. The problem is tackled by implementing a multi-objective optimization (MOO) approach, whose aim is to minimize near-end and far-end crosstalk, namely NEXT and FEXT. The effectiveness of the proposed approach is verified by considering a minimized interconnection system involving an FFC. The Pareto-optimal solutions are identified, and worst-case and best-case conditions are highlighted. The results show improvements in EMC and SI, underlining the relevance of the proposed optimization strategy. The proposed strategy provides a valuable tool for designing high-performance interconnections in electrical and electronic systems.